Formula

Triangular Pyramid
Area of the base (A) = ½ * a * s
Surface Area of Pyramid = A + ((3/2) sl)
Volume of Pyramid = (1/6) abh
Where,
a= apothem length
s= side length
sl= slant height
abh area of base * height

 

Square
Area of the base (A) [s²]
Surface Area of Pyramid = [s² + 2sl]
Volume of Pyramid = [(1/3)b²h ]
Where,
s= side length
sl= slant height
b= base
h= height

Pentagonal
Area of Base : [(5/2)as]
Surface Area of Pyramid : [ (5/2)as + (5/2)sl ]
Volume of Pyramid : [ (5/6)abh]
Where,
As = area of side length
sl= slant height
abh area of base * height

Hexagonal
Area of Base: [(6/2) as]
Surface Area of Pyramid: [3as + 3sl]
Volume of Pyramid: [abh ]
Where,
As = area of side length
sl= slant height
abh area of base * height